Strategi Pengembangan Agrowisata Berkelanjutan di Kawasan Waduk Batujai, Kabupaten Lombok Tengah - Fatman Nurjan; Nurhayati; Sukuryadi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Batujai Dam Reservoir is a vital water resource infrastructure in Central Lombok Regency with significant potential as a sustainable agrotourism destination; however, its development remains suboptimal. This study aims to identify internal and external factors and formulate sustainable agrotourism development strategies in the Batujai Reservoir Area to support environmental conservation, local economic development, and sustainable regional management. A qualitative-descriptive approach with SWOT analysis was employed through in-depth interviews, field observations, and questionnaires directed at local communities and stakeholders. Results indicate that key strengths include the scenic reservoir landscape, local agricultural activities, and strategic positioning as a gateway to the Mandalika Special Economic Zone. Main weaknesses encompass limited tourism infrastructure and low human resource capacity in tourism management. Opportunities include growing trends in educational nature-based tourism and supportive government policies, while the primary threats are environmental degradation and competition from other tourist destinations. The SWOT matrix yielded four strategic groups: SO (integrated agrotourism package development based on local potential), WO (tourism infrastructure development and human resource capacity building), ST (carrying-capacity-based environmental management), and WT (regulatory and institutional strengthening). The priority strategy is integrated agrotourism development emphasizing education, conservation, and local community empowerment. The proposed strategy also promotes sustainable utilization of natural resources, protection of reservoir ecosystem functions, and enhancement of environmental awareness among local communities and visitors. These findings provide empirical contributions to sustainable tourism destination planning in reservoir-based areas across Indonesia.